Effects of Strategic Investment Decisions on Value of Firm: Evidence from India. Issue 1 (June 2019) - Kaur, Parmjit; Kaur, Randeep
The study has captured the effects of announcements of strategic investment decisions on market value of firm and also established the relationship between market value and firm-specific variables. The study is based on strategic investment announcements made by BSE-500 firms, and final sample for the study consists of 581 strategic investment announcements made by 217 firms. These decisions have been classified into seven categories. In order to examine the reaction of share prices to the strategic investment announcements, the event study methodology (Brown and Warner, Journal of Financial Economics, 14, 3–31, 1985; MacKinlay, Journal of Economic Literature, 35, 13–39, 1997) has been applied. The relationship between abnormal returns and independent variables is examined with multiple regression analysis. The results provide strong evidence that the strategic investment decisions' announcements in India contain a positive information signal, and these are perceived as value-enhancing decisions by the investors. The results also help to improve the understanding of how different firm-specific factors may influence market reaction to announcements of strategic investment decisions.